Associations of substance use and positive coping behaviors with sleep quality during the COVID-19 pandemic - Laudie, Jessica; Stangl, Bethany L.; Gunawan, Tommy; Schwandt, Melanie L.; Cheng, Cecilia; Gilmore, Amanda K.; Goldman, David; Ramchandani, Vijay A.; Diazgranados, Nancy; Luk, Jeremy W. (Frontiers in Sleep, 2025)
BackgroundThe COVID-19 pandemic may have negatively impacted individuals' sleep quality. In this study, we examined changes in sleep quality from before to during the COVID-19 pandemic by history of alcohol use disorder (AUD) and investigated the cross-sectional associations of substance use and positive coping behaviors with sleep quality domains.MethodsData were drawn from the NIAAA COVID-19 Pandemic Impact on Alcohol Study which enrolled participants from June 2020 to December 2022. Participants (N = 373, 50.9% male, mean age = 43.7, 37.3% with AUD history) reported their sleep quality using the Pittsburgh Sleep Quality Index (PSQI) for the month prior to the pandemic and the past month before the time of assessment. Multilevel modeling and linear regression analyses were conducted.ResultsIndividuals with AUD history reported worse overall sleep quality than those without AUD history both before and during the pandemic. Individuals without AUD history reported an overall increase in PSQI scores (worsened sleep quality) across time. AUD history and substance use behaviors due to the pandemic were associated with worse sleep quality. Conversely, positive coping behaviors (e.g., take care of body, make time to relax, connect with others, multiple healthy behaviors) were associated with better sleep quality domains.ConclusionsAUD history, substance use, and positive coping behaviors were correlated with sleep quality during the pandemic. These findings may offer insight into behavioral targets to improve sleep quality in the context of significant stress exposure and can help improve preparedness for future public health crises.